Design and Fabrication of a Liver-on-a-chip Reconstructing Tissue-tissue Interfaces - Liu, Jing; Feng, Chong; Zhang, Min; Song, Feng; Liu, Haochen (Frontiers in Oncology, 2022)
Despite the rapid advances in the liver-on-a-chip platforms, it remains a daunting challenge to construct a biomimetic liver-on-a-chip for in vitro research. This study aimed to reconstruct the tissue-tissue interfaces based on bilayer microspheres and form vascularized liver tissue. Firstly, we designed a tri-vascular liver-on-a-chip (TVLOC) comprising a hepatic artery, a portal vein and a central vein, and theoretically analyzed the distribution of velocity and concentration fields in the culture area. Secondly, we designed a bilayer microsphere generating microsystem based on the coaxial confocal principle, which is primarily used to produce bilayer microspheres containing different kinds of cells. Finally, the bilayer microspheres were co-cultured with endothelial cells in the cell culture area of the TVLOC to form vascularized liver tissue, and the cell viability and vascular network growth were analyzed. The results revealed that the TVLOC designed in this study can provide a substance concentration gradient similar to that of the liver microenvironment, and the bilayer microspheres can form a three-dimensional (3D) orderly liver structure with endothelial cells. Such a liver-on-a-chip is capable of maintaining the function of hepatocytes (HCs) pretty well. This work provides full insights into further simulation of the liver-on-a-chip.